2016
DOI: 10.1270/jsbbs.66.60
|View full text |Cite
|
Sign up to set email alerts
|

Persimmon breeding in Japan for pollination-constant non-astringent (PCNA) type with marker-assisted selection

Abstract: Oriental persimmon (Diospyros kaki) originated in Eastern Asia, and many indigenous cultivars have been developed in China, Japan, and Korea. These cultivars are classified into four groups based on their natural astringency loss on the tree and seed formation: pollination-constant non-astringent (PCNA), pollinationvariant non-astringent (PVNA), pollination-constant astringent (PCA), and pollination-variant astringent (PVA). PCNA is the most desirable type because the fruit can be eaten without any postharvest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 30 publications
3
31
0
Order By: Relevance
“…Persimmon growing regions are also spreading widely in Japan and Korea, thus some old well-known Persimmon varieties which were still being produced were selected from these countries. Persimmon has been a major fruit crop in Japan for many years [21] and for Japanese persimmon commercial production, 'Fuyu' (PCNA), 'Hiratanenashi' (PVA) and 'Tonewase' have been the three important cultivars. About 57% of the total area is devoted to these varieties [22].…”
Section: Commercial and Recently Improved Persimmon Varietiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Persimmon growing regions are also spreading widely in Japan and Korea, thus some old well-known Persimmon varieties which were still being produced were selected from these countries. Persimmon has been a major fruit crop in Japan for many years [21] and for Japanese persimmon commercial production, 'Fuyu' (PCNA), 'Hiratanenashi' (PVA) and 'Tonewase' have been the three important cultivars. About 57% of the total area is devoted to these varieties [22].…”
Section: Commercial and Recently Improved Persimmon Varietiesmentioning
confidence: 99%
“…Although persimmon is produced in Brazil, Israel, Italy, Spain, Azerbaijan, Uzbekistan, New Zealand and Australia, new persimmon cultivars developed by cross breeding have been released only in Japan and Korea [21] and also in these countries persimmon cultivars have been selected over time for commercial production. Hybridization method can also be used in persimmon breeding.…”
Section: Persimmon Breeding and Genetic Improvementmentioning
confidence: 99%
“…The commercial significance of the astringency characteristic has led to the development of molecular markers co-segregating with the PCNA trait; these markers are being extensively used in ongoing breeding programs (Kanzaki et al, 2010;Sato and Yamada, 2016). To date, however, genetic mapping of AST has not been completed partly because of the high heterozygosity, long juvenile phase, and complex allelic composition of the D. kaki polyploid genome (mainly 2n = 6x = 90).…”
Section: Introductionmentioning
confidence: 99%
“…Among the four classes, PCNA type cultivars stop accumulating PAs in the early stages of fruit development by down-regulation of enzymes in the PA biosynthesis pathway (Akagi et al, 2009a;Ikegami et al, 2005;Yonemori and Matsushima, 1985). This PCNA trait has been targeted in modern persimmon breeding programs in Japan to reduce the need for labor-intensive and expensive artificial de-astringency treatments that are required to render non-PCNA fruit palatable for consumers (Sato and Yamada, 2016). It has been shown that the PCNA trait is conferred by a recessive allele (ast) at a single locus referred to as ASTRINGENCY (AST) (Akagi et al, 2012;Ikeda et al, 1985;Yamada and Sato, 2002).…”
mentioning
confidence: 99%
See 1 more Smart Citation